A política urbana e o acesso à moradia adequada por meio da regularização fundiária - Casimiro, Lígia Maria Silva Melo de (2010)
The Democratic State of Law takes the fundamental rights as base in its normative structure, defined in a detached way in the Constitution of 1988. The constitutional routes for the landed regularization has as core the development and promotion of the social right of land, always in harmony with the environment, in which the city has to execute you function and allow that everyone use it. The Statute of the City describes in detail the aspect of such politics proposing the balance in the service of promotion the right of the adequate housing and the respect and protection to the natural environment, not neglecting, specially, the irregular dwellings in small and great cities of the country. The instrument to look for the balance proposed by the new urbane politics is the landed regularization, which will have to give security and worthy conditions of dwelling to the destitute population, driving the public administrator to observes the treatment given by the laws of town planning and environmental content, exercising his administrative function by the light of the constitutional and (infra)constitucional foresight. The administrative function needs to act as to provide the public interests in the promoting of the appropriate right of habitation trough the regularization action, allowing better conditions of life for the population of low revenue